PENYULUHAN PEMANFAATAN KELAPA MENJADI PRODUK KESEHATAN VIRGIN COCONUT OIL DI DESA OUW, KECAMATAN SAPARUA TIMUR, KABUPATEN MALUKU TENGAH - Sipahelut, Sophia Grace; Lawalata, Vita Novalin (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
Virgin coconut oil (VCO) is known and believed to be the healthiest oil in the world because it contains medium chain fatty acids which contribute to health. However, the process of making VCO is not yet familiar to the community, especially in Ouw Village, East Saparua District, Central Maluku Regency. Even though the potential for coconuts in this village is quite abundant. The aim of this service activity is to provide information and knowledge to the people of Ouw Village, East Saarua District, Central Maluku Regency about the technology for processing coconuts into VCO. This community service activity was attended by 45 housewives and young women. Activities are carried out in the form of counseling and evaluation. The outreach activities carried out received a positive response from participants. People are very happy to gain knowledge about the technology for making VCO as a healthy product and are enthusiastic about making it themselves and consuming it by their own families.